Effect of PFA on strength and water absorption of mortar - G.S., Gingos; Norsuzailina, Mohamed Sutan (UNIMAS Publisher, 2022)
Partial replacement of cement by mineral admixtures or pozzolans can possibly improve the durability of mortar which directly related to its water absorption. Pulverized Fuel Ash (PFA) is one of the pozzolans that is locally available. Laboratory studies have been conducted on mortar mixes of 0.3w/c, 0.4w/c and 0.5w/c ratios with 10%, 20% and 30% PFA replacements. Mortar cubes were tested to determine their water absorption rates and compressive strengths as they mature. Amount of PFA replacements in the mortar has significant effects on the strength development and water absorption rate of the mortar. Results shows that 20% PFA mortars of 0.5w/c ratio is the best mix to reduced rate of water absorption and achieved higher compressive strength.